Impact of video-endoscopy on the results of retrosigmoid-transmeatal microsurgery of vestibular schwannoma: prospective study - Chovanec, Martin; Zvěřina, Eduard; Profant, Oliver; Skřivan, Jiří; Cakrt, Ondřej; Lisý, Jiří; Betka, Jan (European archives of oto-rhino-laryngology, 2013)
Endoscopy-assisted microsurgery represents modern trend of treatment of the cerebellopontine angle (CPA) pathologies including vestibular schwannoma (VS). Endoscopes are used in adjunct to microscope to achieve better functional results with less morbidity. Angled optics, magnification and illumination enable superior view in the operative field. Consecutive 89 patients with untreated unilateral sporadic vestibular schwannoma undergoing tumor resection via a retrosigmoid approach during 2008-2010 were prospectively analysed. Endoscopy-assisted microsurgical (EA-MS) removal was performed in 39 cases (Grade 1: 2, Grade 2: 5, Grade 3: 9, Grade 4: 22, Grade 5: 1) and microsurgical (MS) removal was performed in 50 cases (Grade 1: 1, Grade 2: 3, Grade 3: 9, Grade 4: 34, Grade 5: 3). Minimally invasive approach with craniotomy ≤ 2.5 cm was employed for small tumors (Grade 1 and 2) in the EA-MS group. Endoscopic technique was used for monitoring of neuro-vascular anatomy in CPA, during dissection of the meatal portion of tumors, assessment of radicality and for identification of potential pathways for CSF leak formation. All cases in MS group were deemed as radically removed. In the EA-MS group, residual tumor tissue in the fundus of internal auditory canal not observable with microscope was identified with endoscope in four cases. Such cases were radicalized. Tumor recurrence was not observed during the follow-up in EA-MS group. There is a suspicious intrameatal tumor recurrence on the repeated MRI scan in one patient in the MS group. Neither mortality nor infection was observed. The most common complication was pseudomeningocele (EA-MS 20 cases; MS 23). It was managed with aspiration with or without tissue-gluing in all cases without the need for any surgical revision. Adjunctive use of endoscope in the EA-MS group identified potential pathways for CSF leak formation, which was not observable with the microscope in five patients. Improved cochlear nerve (EA-MS: 22, MS: 14; p = 0.012), brainstem auditory evoked potentials (EA-MS: 3 of 8, MS: 0 of 4) and hearing (EA-MS: 14 of 36, MS: 4 of 45; p = 0.001) preservation were observed in EA-MS group. Despite the trend for better useful hearing (Gardner-Robertson class 1 and 2) preservation (EA-MS: 8 of 26, MS: 1 of 16) there were no significant differences in the postoperative hearing handicap inventory in both groups. There were no differences in the postoperative tinnitus in both groups. Better facial nerve preservation (EA-MS: 39, MS: 44; p = 0.027) and excellent-very good (House-Brackmann 1 or 2) facial nerve function (EA-MS: 31, MS: 29; p = 0.035) were observed in EA-MS group. Postoperative compensation of vestibular lesion, symptoms typical for VS, patients assessed by dizziness handicap inventory, facial disability index were comparable in both studied groups. Adjunctive use of endoscope during the VS surgery due to its magnification and illumination enable superior view in the operative field. It is valuable for assessment of radicality of resection in the region of internal auditory meatus. Improved information about critical structures and tumor itself helps the surgeon to preserve facial nerve and in selected cases also hearing. These techniques can help to decrease incidence of postoperative complications.
Keywords: senioři; endoskopie; Evoked Potentials, Auditory, Brain Stem; Middle Aged; mužské pohlaví; Prospective Studies; Adult; mladý dospělý; Neuroma, Acoustic; Postoperative Complications; Craniotomy; Endoscopy; magnetická rezonanční tomografie; Magnetic Resonance Imaging; Young Adult; ženské pohlaví; kraniotomie; Humans; prospektivní studie; Cochlear Nerve; vestibulární schwannom; lidé středního věku; Video Recording; sluchové kmenové evokované potenciály; mikrochirurgie; nervus cochlearis; dospělí; Vestibular Nerve; nervus vestibularis; Female; Aged; Microsurgery; pooperační komplikace; lidé; Male; audiovizuální záznam